Stability and Change in One Adult's Second Language English Negation. Issue 3 (7th June 2013) - Hauser, Eric
<x xml:space="preserve">Abstract</x> This article reports on how, against a background of relatively stable patterns of second language negation, a Japanese‐speaking adult learning English made use of a negative formula, "I don't know, " and how, in and through interaction, analyzed it into its component parts and began using "don't" more productively. Making use of the micro‐analytic techniques of conversation analysis to analyze data collected over a seven‐month period, two relatively stable patterns of negation are described. This is followed by a description of how the learner used the formula and, over time, analyzed it. This often involved repetition and/or self‐repair. Changes in how "don't" was used included coming to use it with the verb "like, " as well as coming to use it with "you."